Effect of Storage Treatment on Small White Ginger Rhizome Viability - Melati Melati; Devi Rusmin (Universitas Djuanda Bogor, 2018)
One problem for developing small white ginger (Zingiber officinale var. amarum) is theavailability of high quality rhizome seeds in right quantity and time. Seed rhizome will sproutquickly, and its quality will decreased in immature seed rhizome and in not good storage conditions.The main objective of the experiment was to study the best storage room conditions for storagerhizome seeds of small white ginger. The experiment was conducted in seed laboratory and storageroom of Research Institute for Medicinal and Aromatic Crops Bogor. The experiment wasconducted by randomized complete design with nine different storage, 3 replication and 25 sampleseach treatment. The treatments are 1) rhizome seeds storage in room temperature (control),(2)rhizome seeds storage in AC room (16–240C),(3) rhizome seed soaked in paclobutrazol 1000 ppmfor 4 hours then seeds storage in room temperature ( 4) put rhizome seeds in rack and cover bystraw, storage in room temperature (5) rhizome seed storage on straws in the greenhouse ( 6)rhizome seed storage in the greenhouse without straw ( 7) rhizome seed soaked in water during 1hour every month then dried naturally in 300C and storage in AC room (8) rhizome seed soakedin paclobutrazol 1000 ppm for 4 hour then storage in AC room ( 9) put rhizome in wood box andcover by rice straw and husk. Variables observed include moisture contents of ginger seed, lostweight of seed and germination percentage of rhizome seeds at the end of storage period. The resultof experiment indicated that the moisture content and weight rhizome seeds decrease after 2 months. After four months storage period, moisture content was still high above 80 %, exceptrhizome seeds in under ground. The rhizome seeds that store in AC room showed the bestperformance and thus, this treatment can be recommended for storage of small white gingerrhizome seeds for 4 months. The low moisture content (< 80%) of rhizome small white ginger seedswill decreased its viability.Keywords: Zingiber officinale var. amarum, seed, storage, viability